Determination of Gossypol in Poultry Egg and Feed by Automated Solid-Phase Extraction and High-Performance Liquid Chromatography - Shi, Zu-Hao; Tang, Meng-Jun; Zhang, Xiao-Yan; Tao, Zhi-Yun; Wu, Ming; Gao, Yu-Shi; Gu, Rong; Lu, Jun-Xian; Pu, Jun-hua; Ge, Qing-Lian (Asian Journal of Chemistry, 2013)
A high-performance liquid chromatographic method for the determination of gossypol in poultry egg and feed was developed. Gossypol was extracted with 90 % acetonitrile/water (v/v) in presence of ascorbic acid and purified by C18 cartridge with automated solid-phase extraction system. The samples were separated through an optimized chromatography condition on a C18 column (4.6 mm × 250 mm, 5 μm particle) and UV detection at 235 nm. A gradient with acetonitrile and water containing 0.1 % phosphoric acid was applied. The method was shown to be highly reproducible, with overall recovery was 89.5 % and relative standard deviation was 8.7 %.